Using qualitative methods in pilot and feasibility trials to inform recruitment and retention processes in full-scale randomised trials: a qualitative evidence synthesis - Shaun Treweek; Karin Hannes; Katie Gillies; Cynthia Fraser; Hanne Bruhn; Adel Elfeky (BMJ Open, 2022)
Objectives To systematically review published pretrial qualitative research studies and explore how their findings were used to inform recruitment and retention processes in full-scale trials.Design Qualitative evidence synthesis using thematic analysis.Data sources and eligibility criteria We conducted a comprehensive search of databases; Dissertation Abstracts International, CINAHL, Embase, MEDLINE, Sociological Abstracts and PsycINFO. We included all reports of pretrial qualitative data on recruitment and retention in clinical trials up to March 2018.Data extraction and synthesis Two authors independently extracted data using a predefined data extraction form that captured study aims, design, methodological approach and main findings, including barriers and facilitators to recruitment and or retention. The synthesis was undertaken using Thomas and Harden’s thematic synthesis method and reported following the Enhancing Transparency in Reporting the Synthesis of Qualitative Research guidelines. Confidence was assessed using Grading of Recommendations Assessment, Development and Evaluation-Confidence in the Evidence from Reviews of Qualitative research approach.Results Thirty-five papers (connected to 31 feasibility studies) from three different countries, published between 2010 and 2017 were included. All studies were embedded in pilot or feasibility studies to inform design aspects in preparation for a subsequent full-scale trial. Twelve themes were identified as recruitment barriers and three as recruitment facilitators. Two themes were identified as barriers for retention and none as retention facilitators. The findings from qualitative research in feasibility or pilot trials are often not explicitly linked to proposed changes to the recruitment and retention strategies to be used in the future or planned full-scale trial.Conclusions Many trial teams do pretrial qualitative work with the aim of improving recruitment and retention in future full-scale trials. Just over half of all reports of such work do not clearly show how their findings will change the recruitment and retention strategy of the future trial. The scope of pretrial work needs to expand beyond looking for problems and also look for what might help and spend more time on retention.